Dietary isothiocyanates and anticancer agents: exploring synergism for improved cancer management - Wang, Qi; Li, Dan; Liu, Lihua; Shan, Yujuan; Bao, Yongping (Frontiers in Nutrition, 2024)
Human studies have shown the anticancer effects of dietary isothiocyanates (ITCs), but there are some inconsistencies, and more evidence supports that such anticancer effect is from higher doses of ITCs. The inconsistencies found in epidemiological studies may be due to many factors, including the biphasic dose-response (so called hormetic effect) of ITCs, which was found to be more profound under hypoxia conditions.In this comprehensive review, we aim to shed light on the intriguing synergistic interactions between dietary ITCs, focusing on sulforaphane (SFN) and various anticancer drugs. Our exploration is motivated by the potential of these combinations to enhance cancer management strategies. While the anticancer properties of ITCs have been recognized, our review delves deeper into understanding the mechanisms and emphasizing the significance of the hormetic effect of ITCs, characterized by lower doses stimulating both normal cells and cancer cells, whereas higher doses are toxic to cancer cells and inhibit their growth.We have examined a spectrum of studies unravelling the multifaceted interaction and combinational effects of ITCs with anticancer agents. Our analysis reveals the potential of these synergies to augment therapeutic efficacy, mitigate chemoresistance, and minimize toxic effects, thereby opening avenues for therapeutic innovation. The review will provide insights into the underlying mechanisms of action, for example, by spotlighting the pivotal role of Nrf2 and antioxidant enzymes in prevention. Finally, we glimpse ongoing research endeavors and contemplate future directions in this dynamic field. We believe that our work contributes valuable perspectives on nutrition and cancer and holds promise for developing novel and optimized therapeutic strategies.